Gender-based political violence: a comparative legal analysis of Brazil, Bolivia, Mexico and Portugal (Revista do Tribunal Regional Federal da 3ª Região, 2026)
This article analyzes gender-based political violence through the lens of Comparative Law, focusing on the legal frameworks of Brazil, Bolivia, Mexico, and Portugal. The study aims to understand how these jurisdictions normatively address violence directed at women in political contexts, emphasizing the effectiveness, scope, and limitations of current statutes. Initially, the research conceptualizes gender-based political violence and contextualizes its relationship with patriarchal and symbolic structures of domination. Subsequently, it examines Brazilian Law No. 14,192/2021, which criminalizes such violence, highlighting advancements and gaps, such as the lack of protection for pre-candidates and transgender women. Furthermore, the study compares the Brazilian legislation with the legal frameworks of Bolivia, a pioneer in this field; Mexico, which adopted a comprehensive and sanction-based model; and Portugal, serving as a counterpoint as it lacks a specific law on political violence against women. The methodology is qualitative, exploratory, analytical, and comparative, based on literature review, statutory analysis, and statistical data. The findings reveal that even in countries with greater female representation and robust legal frameworks, violence persists despite significant normative progress. The study concludes that, beyond legal instruments, it is essential to implement structural public policies, civic education, and mechanisms to guarantee women’s political participation under conditions of equality, safety, and permanence.
Keywords: Comparative electoral law; political rights; gender-based political violence; women's political representation; gender equality